Malignant change in dermatitis artefacta. Issue 814 (August 1993) - Alcolado, J. C.; Ray, K.; Baxter, M.; Edwards, C. W.; Dodson, P. M.
Abstract : Dermatitis artefacta is a chronic skin lesion produced by self-trauma. Avoidance of further trauma, topical steroids and psychological therapy all play a part in the treatment of such lesions. Unresolved lesions may become large and disfiguring and subject to infection. We report a case of one such lesion in an elderly woman who persistently excoriated a cholecystectomy scar over 40 years. Malignant transformation occurred in a manner analogous to the neoplastic change observed in other types of chronic ulcer (Marjolin's ulcer). The squamous cell carcinoma presented with widespread metastases from which the patient eventually died. Recent literature concerning Marjolin's ulcers is reviewed and it is noted that this is the first reported case of death caused by malignant change in dermatitis artefacta.